2D and 3D phase mapping of laser interacted interferograms - Yahaya, Asiah (Faculty of Science, 2009)
Phase mapping is a tool for obtaining the different physical quantities from an interferogram. However, phase mapping of laser interacted interferogram can often lead to phase ambiguity which fails to meet the true physical quantities of the event. This usually occurs when measurement is made using only a single interferogram. To overcome the problem, a three-interferogram system was developed in this work. Three simultaneously-captured interferograms were processed using the chosen algorithm. With Mathcad programming, 2D and 3D phase changes from a laserinteraction event represented in the three-interferograms were successfully mapped